PHCOG MAG.: Research Article Blood Glucose level Lowering Activity of Sri Lankan Black Tea brew (Camellia sinensis) in rats - Jayakody, J.R.A.C.; Ratnasooriya, W.D. (My University, 2008)
ABSTRACT This study examined the blood glucose level [owering ability of black tea brew (BTB) of Sri Lankan Camellia sinensis (L.) O.Kuntze {Family: Theaceae). This was tested in normoglycaemic and streptozotocin induced diabeUc rats using high grown Dust grade No: 1 t ea (doses used: 84 mg / m l , equivalent to 1.5 cups; 168 m g / m l , equivalent to 3 cups; and 501 m g / m l , equivalent to 9 cups, orally). The results show that BTB possess promising and significant (P < 0.05) hypoglycaemic (both in normoglycaemic fasted rats and non fasted rats), antihyperglycaemic (in terms of improved glucose tolerance test), and antidiabetic (when tested in streptozotocin induced diabetic rats) activities. BTB (only highest dose tested) also exhibited a-glu^osidase inhibitory activity (in terms of sucrose tolerance test) inhibited glucose absorption from the lumen of small intestine and possessed marked antioxidcnt activity in vitro (in terms of DPPH assay). On t he other hand, the highest dose failed to increase insulin output and glycogen content in liver and skeletal muscle, it is concluded that BTB made from Sri Lankan black l e a ha:, blood glucose lowering activity in both normoglycaemic and diabetic status. KEY WORDS- Camellia sinensis, antidiabetic, hypoglycaemia, antihyperglycaemia,